Key Elements in Integrity Management of Underground Gas Storage: A Framework for Energy Safety - Shuyi Xie; Bin He; Ligang Chen; Kangkai Xu; Jinheng Luo; Lifeng Li; Bohong Wang (Energies)
Gas reservoir-type underground gas storage (UGS) plays a critical role in China’s natural gas reserves and peak shaving, serving as an essential component of the energy security system. Its unique cyclic injection and production operations not only stabilize the natural gas supply but also impose stringent requirements on the safety and integrity of geological structures, wellbores, and surface facilities. Weaknesses in current practices can cause accidents, directly threatening energy security. Therefore, continuously improving integrity management is the key to mitigating energy risks. Currently, the integrity management of gas storage faces challenges such as an abundance of standards and the complexity of management elements, which affect both operational safety and management efficiency. To address these issues, this study systematically analyzes domestic and international standards related to gas storage and establishes a technical system based on “three-in-one” integrity management (geological structure, wellbore, and surface facilities). Key elements of integrity management are identified and optimized, and recommended execution standards for critical factors are proposed to provide a theoretical basis and decision-making support for the safe operation of gas storage. This study not only offers a reference for optimizing and implementing integrity management standards but also has significant practical implications for enhancing energy security and reducing energy risks, ensuring the smooth execution of China’s natural gas reserve and peak shaving initiatives.